Intense variability of dissolved oxygen and temperature in the internal swash zone of Hamilton Harbour, Lake Ontario. Issue 2 (3rd April 2021) - Flood, Bryan; Wells, Mathew; Midwood, Jonathan D.; Brooks, Jill; Kuai, Yulong; Li, Jingzhi
ABSTRACT: The thermocline of large, stratified lakes is constantly sloshing along the sloping bed, creating a spatially variable internal swash zone. Temperature and dissolved oxygen vary rapidly here, potentially impacting fish habitat on timescales of hours. Large spatial differences in the time-dependent variance of temperature around Hamilton Harbour, Lake Ontario, Canada, were partly controlled by basin shape and bathymetry. The temporal variability was nearly twice as large at sites along the mildly sloping, narrow, upwind end of the basin relative to those at a similar depth at the steeper, broad, downwind end. Because the thermocline and oxycline were coincident, the same physical mechanisms resulted in a dissolved oxygen variance also twice as great at the mild slope compared to the steeper slope. Frequent hypoxic events occurred throughout the internal swash zone, drastically reducing the availability of fish habitat for anoxia-intolerant species. In the dynamic littoral zone, weekly measurements would overlook the acute temporal variability of temperature and dissolved oxygen. Here, we demonstrate that field observations and 3-dimensional (3D) hydrodynamic modelling can predict how basin morphometry affects internal seiche dynamics and spatial variability of internal swash zones.